Native Grasslands at the Core: A New Paradigm of Intensification for the Campos of Southern South America to Increase Economic and Environmental Sustainability - Jaurena, Martín; Durante, Martín; Devincenzi, Thais; Savian, Jean V.; Bendersky, Diego; Moojen, Fernanda G.; Pereira, Marcelo; Soca, Pablo; Quadros, Fernando L. F.; Pizzio, Rafael; Nabinger, Carlos; Carvalho, Paulo C. F.; et al. (Frontiers in Sustainable Food Systems, 2021)
Extensive livestock production in southern South America occupies 0.5M km2 in central-eastern Argentina, Uruguay and southern Brazil. These systems have been sustained for more than 300 years under year-long grazing of the highly biodiverse native Campos ecosystems, but are at risk of land use conversion. Their productivity is low (60-70 kg liveweight/ha-1), at least relative to potential records in experiments, which increases their vulnerability to land use change. There is a pressing need for usable, cost effective technological options based on scientific knowledge that increase profitability while supporting the conservation of native grasslands and the many ecosystem services they provide.". In the early 2000s, existing knowledge was synthesized in a path of six sequential steps of increasing intensification. Even though intensified productivity underlined that path, it was already recognized that trade-offs would occur, with increases in productivity being concomitant to reductions in diversity, resilience to droughts, and a higher exposure to financial risks. Here, we put forward a proposal to shift the current paradigm away from a linear sequence and towards a flexible dashboard of intensification options to be implemented in defined modules within a farm whose aims are (i) to maintain native grasslands as the main feed source, and (ii) ameliorate its two major productive drawbacks: marked seasonality and relatively rapid loss of low nutritive value – hence the title: “native grasslands at the core”. We sum up experimental evidence and case studies supporting the hypothesis that designing systems that integrate intensification options increases profitability and environmental sustainability of livestock production systems in Campos ecosystems. At its center, the proposal highlights a key role for optimal grazing management of native grasslands to maintain low system wide costs and financial risks, and to increase productivity and resilience, but acknowledges that for most farms achieving the required spatio-temporal control of grazing intensity requires using (a portfolio of) complementary, synergistic intensification options.